IMF Staff papers : Volume 13 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1966)
This paper focuses on private capital movements and exchange rates in developing countries. The paper also highlights some implications of the analysis about the broader question of the effect of alternative exchange rate systems on capital flows. Capital movements respond to many factors which affect the yields expected by investors. Some of these, such as changes in the structure of the economy of the investee country, discoveries of mineral deposits, changes in exchange control or tax systems, the passage of investment laws, the amount of-and experience with-previous investments in the country, and, not least, the country's potential for economic growth, are very likely to play a more dominant role in the investment decision than expectations of changes in prices or exchange rates. The expectation of changes in the foreign exchange rate and in domestic prices and costs influences private capital movements, other things being equal, by altering the expected rate of return on assets which foreign investors may hold in the investee country.